Strengthening MSMEs Competitiveness through Branding-Based Product Packaging Training and Mentoring - Tarso; Deny Hadi Siswanto; Rohmanur Mala; Rif'an Efendi (Pustaka Bangsa Indonesia, 2026)
This community service program aimed to improve the knowledge, skills, and capacities of Micro, Small, and Medium Enterprise (MSME) owners in Kalasan District in developing attractive, informative, and value-added product packaging. The program employed a participatory approach through needs assessment, material preparation, training, packaging design practice, and evaluation. The training covered packaging functions and benefits, packaging design, product labeling standards, branding strategies, and the use of packaging as a marketing tool. Evaluation was conducted through observation, interviews, and documentation, which were analyzed descriptively. The results showed improved participants’ understanding of the strategic role of packaging in product protection, brand communication, and marketing. Participants also demonstrated better skills in designing more attractive and competitive packaging, greater awareness of proper labeling standards, and stronger motivation to develop product branding. However, challenges such as limited capital, access to quality packaging materials, and varying digital literacy remain, indicating the need for continuous mentoring to sustain packaging innovation and strengthen MSME competitiveness.